PHATIC FUNCTION IN THE NOVEL “A PORTRAIT OF THE ARTIST AS A YOUNG MAN” BY JAMES JOYCE - Yusniati Sabata; Ibrahim - (Universitas Muhammadiyah Malang, 2018)
Abstract: This study examined the language function occurred in the novel “A Portrait of the Artist as a Young Man” by James Joyce formulated by Jackobson. The aims of the study were to identify and to examine the phatic function that occurs in conversation. This study employed descriptive qualitative methods. Data were collected through the source of the data namely the novel “A Portrait of the Artist as a Young Man” by James Joyce formulated by Jackobson. There are five steps used as the techniques of collecting data, they are (1) read the novel, (2) identified the utterances, (3) collected the phatic function, (4) counted the phatic function, and (5) examined the purpose of the utterances. Triangulation technique was also used to collect the data. This study found nine functions of language as the result of this study, those were, emotive, directive, phatic, poetic, referential, metalinguistic, contextual, emotive and directive, and referential and poetic functions. The purpose of the phatic function that found in conversation namely, opening the channel of communication such as greeting, checking that it is working, asking the social reasons, maintaining the contact of communication, and show a farewell expression.Keywords: Phatic Function, Novel, James Joyce